2015
DOI: 10.1080/02687038.2015.1049584
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making, cognition, and aphasia: developing a foundation for future discussions and inquiry

Abstract: Background: Making a decision is a cognitive task that requires the use of cognitive functions such as attention, memory, language, and executive function. Researchers have found people with cognitive deficits perform worse than healthy controls on experimental measures of decision-making. Researchers have also shown that persons with aphasia (PWA) may have deficits in the cognitive functions implicated in rational decision-making. Aims: In this paper, we will discuss the cognitive processes associated with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 68 publications
(112 reference statements)
0
24
0
Order By: Relevance
“…While Jayes et al () reported that the choice of which MDT members assess capacity may often be decided on perceptions of professional hierarchy and responsibility, it should be guided on the basis of which HCP has more knowledge, skill or information about the decision and the patient. For example, speech and language pathologists have emphasised their specialist skills and their role for people with communication difficulties like aphasia (Aldhous et al, ; McCormick et al, ; Suleman & Kim, ). Therefore, it is not surprising in this study that occupational therapists reported significant involvement in DMC assessment regarding independent living, and less so in other areas, such as sexual consent.…”
Section: Discussionmentioning
confidence: 99%
“…While Jayes et al () reported that the choice of which MDT members assess capacity may often be decided on perceptions of professional hierarchy and responsibility, it should be guided on the basis of which HCP has more knowledge, skill or information about the decision and the patient. For example, speech and language pathologists have emphasised their specialist skills and their role for people with communication difficulties like aphasia (Aldhous et al, ; McCormick et al, ; Suleman & Kim, ). Therefore, it is not surprising in this study that occupational therapists reported significant involvement in DMC assessment regarding independent living, and less so in other areas, such as sexual consent.…”
Section: Discussionmentioning
confidence: 99%
“…Both the language barrier that defines aphasia and any accompanying cognitive issues should be carefully evaluated and circumvented to the extent possible using appropriate communication supports. 21,22 THE PROCESS FOR ESTABLISHING CAPACITY TO MAKE LEGAL AND/ OR CLINICAL DECISIONS When exploring the issue of communication supports, it is important to understand the stages involved in the decision-making process. Zuscak et al 23 provide a three-step decision framework that explicitly includes communication support strategies, as follows: (1) understanding relevant information; (2) appreciating consequences and reasoning; and (3) communicating a choice.…”
Section: Misinterpretation Of the Term Cognitive Impairment In Relatimentioning
confidence: 99%
“…It also has been cited as a method that can be used to support attention and memory processes in a decision-making appraisal. 22 A signature feature of SCA TM is a technique for verifying that information provided by the person with apha-sia is what he/she intends to convey and that it has been understood by the partner. See Table 1 for examples of SCA TM applications, as well as additional communication support strategies that can compensate for both language and cognitive impairments during capacity assessments.…”
Section: Reading Comprehensionmentioning
confidence: 99%
“…According to the dual‐process theory of decision making, for example, rational decision making in typical adults comprises two distinct processes: one is fast, automatic and unconscious (a Type One process) and the other is slow, deliberative and conscious (a Type Two process; Evans, ; Evans & Over, ; Evans & Stanovich, ). This theory highlights that a “Type Two” process is essential for a person to make rational decisions and involves the cognitive functions of working memory and executive function (Evans & Stanovich, ) as well as attention and language (Suleman & Kim, ). When applying this theoretical framework to mental capacity assessment, if a person were unable to engage a Type Two process, this would support a lack of mental capacity.…”
Section: Introductionmentioning
confidence: 99%